The Development of Economic Right Principle Implementation of Trademark Right in The Covid-19 Pandemic Era - Najmi; Delfiyanti (Andalas International Journal of Socio-Humanities, 2021)
The pandemic of Covid-19 that struck since beginning of 2020 had an enormous impact to the whole states in the world including Indonesia. The pandemic was bring worst influences to the economic and trading. The deadly disease automatically was paralyze an economy and trading. It is caused by restriction of people to drive and influences the product movement. Temporarily, export-import activities delayed as restriction of transportation entry among the states. Finally, Indonesia forced close for in and out flight of territory. The situation influence to the implementation of Economic Right of trademark right attach to the import and export products in Indonesia. By the reasons, the study categorized by, first, the development of Economic Right principle implementation of trademark right in the pandemic era. Secondly, the challenge and effort an implementation of Economic Right principle of trademark right in trading at pandemic era. The study uses normative law method by literature study of related material and the data analysis uses qualitative. According of Act No. 20 of 2016, involves Trademarks and Geographical Indications, the trademark right is an exclusive one granted by the state to the owner for a registered brand for a certain period by using the mark or giving permission to other parties for it. However,it is difficult in current conditions to introduce a new trademark to society amid a weak economic situation so that most recognized trademark will be better able to survive amid the economic downturn in the covid-19 pandemic era. The situation result in violation of trademark ownership when a product is given a label from a previously brand so that a lawsuit can be filed. An interested party may file a lawsuit for the cancellation of a registered trademark and the cancellation submitted to the Commercial Court against the owner of the registered trademark.